Time Study for the Commercial Production of Block Frozen Whole Squid/Cuttlefish in 2 kg Pack - A., Ramachandran (Fishery Technology, 2025)
A time study to work out the normal time and standard time required for each element or activity in the commercial production of block frozen whole squid/ cuttlefish was undertaken. A standard flow chart was developed to minimize the handling and processing time and to minimize exposure of the raw material to higher temperatures. The important allowances to be considered in calculating the standard time were identified as personal, standing and fatigue and process allowances. Filling, setting in trays, glazing and loading in trolleys were considered as an integrated and inseparable activity and was found to consume 112.20 min as normal time and 128.47 min as standard time for producing one batch of 220 slabs of 2 kg each. The process cycle time was estimated to be 305 min for the production and storage of 220 frozen blocks of whole squid/cuttlefish. Process cycle time could be further reduced by introducing modern freezers with shorter freezing time and by introducing automation at the post freezing stations.